THE COMPARISON OF TWO BROILER CHICKEN PARTNERSHIP SYSTEMS IN CLOSED HOUSE CAGE - I P. G. G., Adnyana; Mahardika, I G.; Sukanata, I W. (Jurnal Peternakan Tropika; Vol 8 No 2 (2020): Vol. 8 No. 2 Tahun 2020; Mei - AgustusDO - 10.24843/JPT.2020.v08.i02.p14, 2020)
The research aims to determine the comparison of two broiler chicken partnership systems in a closed house cage that was conducted for 2 months from October to November 2019. Variables used in this study include weight gain, feed consumption, depletion, Feed convertion ratio (FCR), Performance index (IP), contract system A and system B. The study uses data for 7 maintenance periods. The research data were analyzed descriptively on aspects of the partnership pattern of the A and B systems and production performance. The results of this study indicate that systems A and B both implement plasma core partnerships and there are differences in bonuses, system A gives FCR, depletion and IP bonuses while system B provides FCR bonuses and market prices. The results of this study also showed the average weight of chickens at the age of 29 days was 1.317 kg/head, the average weight gain of 1.278 kg/head, average consumption of 1,920 kg/head, average FCR value of 1,488, average depletion rate of 2,276 and average performance index broiler chickens at 297,490. Based on the results of the study it can be concluded that system A and system B have differences in the bonus distribution system and the average production performance of the 7 maintenance periods is still below the standard system A and system B. Keywords: partnership system, broiler chickens, closed house